THE INFLUENCE OF AUTOCRATIC LEADERSHIP STYLE, ORGANIZATIONAL CULTURE AND CAREER DEVELOPMENT ON JOB SATISFACTION WITH MOTIVATION AS A MODERATION VARIABLE - Yudhistira Adwimurti; Selfiani Selfiani (Jurnal Ilmiah Manajemen Ubhara, 2023)
The purpose of this study is to examine the influence of autocratic leadership style, organizational culture, and career development on job satisfaction at PT Blue Safir in the era of COVID-19. The population for this study consists of employees of PT Blue Safir. The sampling method used is saturation sampling, with the entire population of 50 respondents, who are employees of PT Blue Safir, being included. This study adopts a quantitative method, where data collection is done through the distribution of questionnaires, which are then analyzed using descriptive statistics, validity and reliability tests, hypothesis testing, and determination coefficientThe overall findings of this study indicate that autocratic leadership style, organizational culture, career development, and motivation have a positive and significant influence on job satisfaction partially. Additionally, the moderation hypothesis test also reveals that motivation strengthens the impact of autocratic leadership style, organizational culture, and career development on job satisfactionKeywords: Autocratic Leadership Style, Organizational Culture, Career Development, Motivation, Job Satisfaction